Dynamics of romantic love : attachment, caregiving, and sex - Mikulincer, Mario; Goodman, Gail S. (Guilford Press, 2006)
Offering an exploration of universal questions, this book examines the interplay of three distinct behavioural systems involved in romantic love. It presents studies that address intimacy, jealousy, self-disclosure, sexual behaviour, partner violence, and other processes in both satisfying and dysfunctional relationships.